Assessment of the Growth and Reproductive Performance of Cloned Pietrain Boars - Junsong Shi; Baohua Tan; Lvhua Luo; Zicong Li; Linjun Hong; Jie Yang; Gengyuan Cai; Enqin Zheng; Zhenfang Wu; Ting Gu (Animals, 2020)
How to maximize the use of the genetic merits of the high-ranking boars (also called superior ones) is a considerable question in the pig breeding industry, considering the money and time spent on selection. Somatic cell nuclear transfer (SCNT) is one of the potential ways to answer the question, which can be applied to produce clones with genetic resources of superior boar for the production of commercial pigs. For practical application, it is essential to investigate whether the clones and their progeny keep behaving better than the “normal boars”, considering that in vitro culture and transfer manipulation would cause a series of harmful effects to the development of clones. In this study, 59,061 cloned embryos were transferred into 250 recipient sows to produce the clones of superior Pietrain boars. The growth performance of 12 clones and 36 non-clones and the semen quality of 19 clones and 28 non-clones were compared. The reproductive performance of 21 clones and 25 non-clones were also tested. Furthermore, we made a comparison in the growth performance between 466 progeny of the clones and 822 progeny of the non-clones. Our results showed that no significant difference in semen quality and reproductive performance was observed between the clones and the non-clones, although the clones grew slower and exhibited smaller body size than the non-clones. The F1 progeny of the clones showed a greater growth rate than the non-clones. Our results demonstrated through the large animal population showed that SCNT manipulation resulted in a low growth rate and small body size, but the clones could normally produce F1 progeny with excellent growth traits to bring more economic benefits. Therefore, SCNT could be effective in enlarging the merit genetics of the superior boars and increasing the economic benefits in pig reproduction and breeding.